2019
DOI: 10.1186/s12711-019-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of genomic BLUP when considering a genomic relationship matrix based on the number of the largest eigenvalues: a simulation study

Abstract: BackgroundThe dimensionality of genomic information is limited by the number of independent chromosome segments (Me), which is a function of the effective population size. This dimensionality can be determined approximately by singular value decomposition of the gene content matrix, by eigenvalue decomposition of the genomic relationship matrix (GRM), or by the number of core animals in the algorithm for proven and young (APY) that maximizes the accuracy of genomic prediction. In the latter, core animals act a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…The stability of genomic evaluations depends on the amount of data and population parameters, provided that no changes are made to the model. When the data are large enough to estimate the value of nearly all independent chromosome segments, the accuracy of genomic predictions will be high ( Pocrnic et al, 2019 ); hence, their persistency and stability will also be high. Independent chromosome segments are DNA regions that are inherited together in linked blocks ( Stam, 1980 ) that are also called linkage disequilibrium blocks ( Muir, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of genomic evaluations depends on the amount of data and population parameters, provided that no changes are made to the model. When the data are large enough to estimate the value of nearly all independent chromosome segments, the accuracy of genomic predictions will be high ( Pocrnic et al, 2019 ); hence, their persistency and stability will also be high. Independent chromosome segments are DNA regions that are inherited together in linked blocks ( Stam, 1980 ) that are also called linkage disequilibrium blocks ( Muir, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of independent chromosome segments corresponds to the number of core animals in the algorithm for proven and young ( APY ; Misztal et al, 2014a ; Pocrnic et al, 2016b ). Pocrnic et al (2019) reported that accuracies were marginally smaller when using 25% instead of 100% of the optimal number of core animals in APY, suggesting that genomic selection acts on clusters of independent chromosome segments rather than on individual independent chromosome segments. In the same study, the authors also showed that a small amount of phenotypic data allowed only the estimation of the largest clusters (i.e., eigenvalues), and that the four largest clusters explained 10% of the variation in G .…”
Section: Introductionmentioning
confidence: 99%
“…When a large amount of information is available, the accuracy may be high enough; therefore, improvements from the incorporation of causative variants are likely to be small for large data sets. When the number of genotyped animals is larger than the number of independent chromosome segments, the accuracy is maximized without SNP weighting/selection [ 70 , 71 , 72 ].…”
Section: Software Methods and Algorithmsmentioning
confidence: 99%
“…Although accuracy is dependent on the proportion of variance explained by the eigenvalues of the GRM, the distribution of eigenvalues is not consistent, and a small percentage of the largest eigenvalues explain the majority of the genetic variation ( Pocrnic et al, 2019 ). Additionally, the animals necessary to explain the largest eigenvalues carry almost the same genomic information.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the animals necessary to explain the largest eigenvalues carry almost the same genomic information. Hence, selection by GBLUP-based models occurs on clusters of independent chromosome segments, not individual chromosome segments ( Pocrnic et al, 2019 ). In pig populations, the segments can be well estimated if there are around 5,000 animals available with very high accuracy (e.g., theoretical EBV accuracy based on prediction error variance) or an equivalent number of animals with less accuracy.…”
Section: Introductionmentioning
confidence: 99%